Morphologic changes and removal of debris on apical dentin surfaces after Nd : YAG laser and diode laser irradiation - Moura-Netto, Cacio de; Maranho de Moura, Abilio Albuquerque; Davidowicz, Harry; Aun, Carlos Eduardo [UNESP]; Santos Antonio, Miriam Porcel do (Mary Ann Liebert, Inc, 2008)
Objective: To verify the effects of laser energy on intracanal dentin surfaces, by analyzing the morphologic changes and removal of debris in the apical third of 30 extracted human teeth, prepared and irradiated with the Nd:YAG laser and diode laser. Background Data: Lasers have been widely used in endodontics. The morphologic changes in dentin walls caused by Nd: YAG and diode laser irradiation could improve apical seals and cleanliness. Materials and Methods: The protocol used for Nd: YAG laser irradiation was 1.5 W, 100 mJ, and 15 Hz, in pulsed mode, and for diode laser was 2.5 W in continuous mode. Each specimen was irradiated four times at a speed of 2 mm/sec with a 20-sec interval between applications. Five calibrated examiners scored the morphologic changes and debris removal on a 4-point scale. Results: In analyzing the scores, there were no statistically significant differences between the two types of laser for either parameter, according to Kruskal-Wallis testing at p = 0.05. The SEM images showed fusion and resolidification of the dentin surface, with partial removal of debris on the specimens irradiated with the Nd: YAG laser and the diode laser, compared with controls. Conclusion: Both lasers promote morphologic changes and debris removal. These alterations of the dentin surface appeared to be more evident in the Nd: YAG laser group, but the diode laser group showed more uniform changes.